Experimental Study of Pathogenic Microorganisms Inactivated by Venturi-Type Hydrodynamic Cavitation with Different Throat Lengths - Zhiyong Dong; Zhaoyu Qin (Journal of the Civil Engineering Forum, 2018)
Based on self-developed Venturi-type hydrodynamic cavitation device with different throat length-radius ratios L/R in Hydraulics Laboratory at Zhejiang University of Technology in China, 4 throat length-radius ratios L/R=10, 30, 60 and 100, and 4 raw water percentages V0/V=25%, 50%, 75%, and 100% were considered, Escherichia coli and total colony count were selected for indicator bacteria, effects of throat length-radius ratio, throat velocity, cavitation time, raw water percentage and cavitation number on inactivating pathogenic microorganism in raw water by hydrodynamic cavitation were experimentally studied. The results showed cavitation damage of cells of pathogenic microorganisms occurred by microjets and shock waves due to cavitation bubble collapse. The lower the flow cavitation number, the higher the killing rate of E. coli and total colony count. When flow velocity was lower or raw water percentage was higher, killing rate gradually increased with increase in throat length-radius ratio; when flow velocity was higher or raw water percentage was lower, killing rate was almost independent of throat length-radius ratio. Inactivated effect of pathogenic microorganisms can be further enhanced by increasing throat velocity or prolonging cavitation time. Hydrodynamic cavitation is a novel disinfection technique for drinking water without disinfection byproducts (DBPs) and no need to add disinfectant.